(untitled) (Journal of Governance and Development (JGD), 2016)
Forest fires in Indonesia have taken a serious attention at both national and international forums. The paper argued that the inability of government to solve the on-going issue of forest fires is due to a conflict of interests between government and private sectors. For example, certain laws and regulations from central government to local government seem to be vague and contradictive to one another. In addition to wague laws, the way these laws and policies are implemented at the federal and local levels also indicate a clear divergent of policy directions. To make matters worst, private organizations that collobarate with government agencies locally or nationally to combat forest fires have their own interests to pursue. One way in which private plantation owners commonly do to reduce cost of planting new palm oil trees is through slash and burned. As a result, a combination of unclear and inconsistent policy directions along with relentless pursuit of private interests reveals no clear solution to the ongoing crisis of forest fires. Despite tough sanctions and penalties that can be imposed on the guilty private plantation owners, the enforcement of those sanctions rarely takes place. Thus, rooting out forest fires seems to go no where as long as government policies are inconsistent and private interests continue to be pursued without regard to environmental and social impacts.